2020
DOI: 10.20546/ijcmas.2020.904.118
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antifungal Activity of Pleurotus pulmonarius, Pleurotus florida and Shizophyllum commune

Abstract: Antifungal activities of the three mushrooms Pleurotus pulmonarius, Pleurotus florida and Schizophyllum commune ethanol extracts were evaluated against some plant pathogenic fungi (Aspergillus flavus, Aspergillus niger and Alternaria solani, Colletotrichum graminicola, Fusarium oxysporum) by using agar well diffusion method. Minimum inhibitory concentration (MIC) was investigated for 1-20 mg/ml concentration to find out the lowest concentration of the sample that inhibits the growth of the test organisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“… Dahima et al (2020) demonstrated that the pleurostrin extracted from the Pleurotus ostreatus is a 7 kDa anti-fungal peptide. It has also been found that the cordymin extracted from the mushroom Cordyceps militaris and Cordyceps sinensis is an anti-inflammatory peptide having a molecular weight of around 10,906 kDa.…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“… Dahima et al (2020) demonstrated that the pleurostrin extracted from the Pleurotus ostreatus is a 7 kDa anti-fungal peptide. It has also been found that the cordymin extracted from the mushroom Cordyceps militaris and Cordyceps sinensis is an anti-inflammatory peptide having a molecular weight of around 10,906 kDa.…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“…Pleurostrin, a 7 kDa anti-fungal peptide, was extracted from Pleurotus ostreatus 42 . An antiinflammatory peptide, cordymin with 10,906 kDa molecular weight was obtained from mushroom Cordyceps sinensis and Cordyceps militaris 43,44 .…”
Section: Peptides and Proteinsmentioning
confidence: 99%